Early selection in open-pollinated Eucalyptus families based on competition covariates - Pavan, Bruno Ettore; Paula, Rinaldo César De; Perecin, Dilermando; Scarpinati, Edimar Aparecido; Candido, Liliam Silvia (Embrapa Informação TecnológicaPesquisa Agropecuária Brasileira, 2014)
The objetive of this work was to evaluate the influence of intergenotypic competition in open-pollinated families of Eucalyptus and its effects on early selection efficiency. Two experiments were carried out, in which the timber volume was evaluated at three ages, in a randomized complete block design. Data from the three years of evaluation (experiment 1, at 2, 4, and 7 years; and experiment 2, at 2, 5, and 7 years) were analyzed using mixed models. The following were estimated: variance components, genetic parameters, selection gains, effective number, early selection efficiency, selection gain per unit time, and coincidence of selection with and without the use of competition covariates. Competition effect was nonsignificant for ages under three years, and adjustment using competition covariates was unnecessary. Early selection for families is effective; families that have a late growth spurt are more vulnerable to competition, which markedly impairs ranking at the end of the cycle. Early selection is efficient according to all adopted criteria, and the age of around three years is the most recommended, given the high efficiency and accuracy rate in the indication of trees and families. The addition of competition covariates at the end of the cycle improves early selection efficiency for almost all studied criteria.

O objetivo deste trabalho foi avaliar a influência da competição intergenotípica em famílias de polinização aberta de Eucalyptus e o seu efeito na eficiência da seleção precoce. Foram realizados dois experimentos, nos quais o volume de madeira foi avaliado em três idades, em delineamento de blocos ao acaso. Dados dos três anos de avaliação (experimento 1, aos 2, 4 e 7 anos; e experimento 2, aos 3, 5 e 7 anos) foram analisados a partir de modelos mistos. Foram estimados: componentes de variância, parâmetros genéticos, ganhos com a seleção, número efetivo, eficiência da seleção precoce, ganho com a seleção por unidade de tempo e coincidência de seleção com e sem uso de covariáveis de competição. O efeito da competição não foi significativo em idades inferiores a três anos, e o ajuste por covariáveis de competição foi desnecessário. A seleção precoce para famílias é eficiente; famílias de hábitos de crescimento tardio são mais vulneráveis à competição, o que prejudica de forma mais pronunciada a sua classificação ao final do ciclo. A seleção precoce mostra-se eficiente de acordo com todos os critérios adotados, e a idade em torno de três anos é a mais recomendada, em razão da alta eficiência e do alto índice de acerto na indicação de árvores e famílias. A adição de covariáveis de competição ao final do ciclo melhora a eficiência da seleção precoce para quase todos os critérios estudados.
Seleção precoce em famílias de polinização aberta de Eucalyptus com base em covariáveis de competição
Keywords: Eucalyptus; competição intergenotípica; testes de progênies; métodos de seleção; Eucalyptus; intergenotypic competition; progeny tests; selection methods